APPLICATION OF ANALYTICAL HIERARCHY PROCESS METHOD FOR EMPLOYEE PERFORMANCE EVALUATION AT PT XYZ - Awaludin, Muryan (Universitas Dirgantara Marsekal Suryadarma, 2020)
This study aims to determine the performance evaluation criteria and employee sub-criteria, and give weight to each criterion and sub-criteria using the Analytic Hierarchy Process (AHP) method. AHP is a methodology that facilitates understanding of complex problems through solving hierarchically ranked parts (approaches and alternatives), calculating and comparing variables through adding views with geometric averages to synthesize a solution. The main criteria obtained from this study are absenteeism or attendance, achievement of work targets, skills or skills, cooperation, and attitudes of employees. The alternatives used are 5 employees in the company. The results of this study indicate that absenteeism as the most important of the criteria is around 0.3794. In addition there is a consistency ratio of around -0.8112. In addition, the results of the study showed that the system built was able to provide the results of calculations automatically in accordance with the results of calculations carried out manually.Â Keywords: AHP, attendance, achievement of work targets, skills, attitudesÂ